Application and Opportunities for Multiple-use Forestry on a Geographical Basis - Rao, V. S. (Indian Forester, 1961)
For the purpose of planning and application of multiple-use forestry, India can be conveniently divided into several regions. The most important are:- ( i) The region of the Himalayan mountains their off-shoots. ( ii ) The submontane region below these mountain systems. These two are considered together as the forests form fairly continuous blocks. (iii) The Western Ghats. (iv) The Eastern Ghats. (v) The minor hill systems and high plateau. (vi) The table-land. (vii) The great plains. (viii) The coastal strips. The Himalayan system is the great reservoir of moisture for the plains of India. These mountains carry some of the most valuable forests which also contain a great wealth and variety of wild life. Already these forests are put to a variety of uses. The Western Ghats play a similar role in respect of the Deccan table-land. Much has to be done in respect of forest protection and rehabilitation of forests in the badly used Eastern Ghats. The minor hill systems, too, carry vast areas of forests. On the proper preservation and multiple-use management of these woodlands depends the future prosperity of this region. Efforts are under way to put this matter on a sound basis. On the coastal strips, considerable work has been done to fix shifting sands by planting casuarina, thus not only saving fertile lands from sand invasion but also providing timber, fuel, and outing amenities for the populations dwelling in these tree-less tracts. In parts of the greater plains, especially in regions less fortunate in respect of rainfall, shelter belts have a great place in preventing loss of fertile top soil through wind lift, and encouraging birds that are of assistance to farmers. A rich and varied wild life is a great feature of the Indian forests. Its conservation can provide first rate amenities in the shape of biological study, sport, photography, adventure etc. Forests and Nature Parks are of great use in countering and correcting the imbalance produced by rapid industrialisation. There is plenty of opportunity for development of these aspects and enlarging the scope for restoration of physical, mental and spiritual health amongst factory-worm populations.